E-COMMERCE SECTOR REVIEW IN THE COVID-19 PERIOD AND STRATEGY RECOMMENDATIONS - YÜCEOL, Nazlı; CAN , Esin; ZEHİR , Cemal; URFA, Ayşe Merve (SSD Journal, 2021)
This study examines the situation faced by the e-commerce industry in Turkey with the Covid-19 outbreak. In the study, the positive and negative developments experienced by the e-commerce sector due to Covid-19, which has become even more important with the pandemic, are analyzed, and the favorable and unfavorable aspects for the development of the sector are analyzed. In this context, first, the SWOT analysis of the e-commerce sector in Turkey was done and the strengths and weaknesses of the sector and the opportunities and threats to the sector were evaluated. Subsequently, the SWOT analysis of the e-commerce sector in Turkey was evaluated in the context of Covid-19. Document analysis and trend analysis methods, which are among qualitative research methods, were used in the research. As a result of the findings, strategy recommendations were made in the context of strengths and weaknesses; opportunities and threats of the sector. As a result of the examinations made, regulations on supply chains, steps to be followed to catch up with the digital age, design of advertising and promotional activities suitable for changing demographics, contactless delivery, artificial intelligence supported cargo solutions, steps to be taken to ensure cyber security, logistics solutions to be followed in response to increasing demand, offensive and defensive strategies that can be followed, can be listed as the prominent topics.